2017
DOI: 10.1177/0975425316683864
|View full text |Cite
|
Sign up to set email alerts
|

The Household Level Determinants in the Choice and Level of Migration

Abstract: Migration decision making of the household is an important dimension in migration literature as it involves the socioeconomic factors of both source and destination places. This study is an endeavour to conceptualize the determinants of choice and level of migration in household migration decision making. It captures both the single location and multiple locations destination option that a prospective migrating family faces while taking migration decision. Applying Heckman two-step technique and McFadden's max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…As such, poorer households would be less likely have out-migrants. These findings are consistent with research outcomes in India [46], Ethiopia [33], and Bangladesh [34], which showed that the households sending migrants were those with relatively higher income levels.…”
Section: Household-level Social and Economic Factorssupporting
confidence: 91%
“…As such, poorer households would be less likely have out-migrants. These findings are consistent with research outcomes in India [46], Ethiopia [33], and Bangladesh [34], which showed that the households sending migrants were those with relatively higher income levels.…”
Section: Household-level Social and Economic Factorssupporting
confidence: 91%
“…Meanwhile, the pull factor was the number of job opportunities within urban areas. This result confirmed earlier findings, in which one of the migration decisions was determined by household income (Chakraborty & Kuri, 2017). However, the migration rate from this village was minimal, whereby the excess labor due to land loss could still be accommodated through existing opportunities in the village, such as jobs in the off-farm and nonfarm sectors.…”
Section: Effect On Migrationsupporting
confidence: 90%
“…Hence, their labour participation level will increase. Improvement of the level of health in married couples can effectively increase their family income (Dustmann and Okatenko, 2014; Chakraborty and Kuri, 2017). Therefore, the effect of equalisation of basic public health and medical services on work income is stronger for married internal migrants.…”
Section: Resultsmentioning
confidence: 99%